The Analysis of Cross-Classified Categorical Data - Fienberg, Stephen E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
A variety of biological and social science data come in the form of cross-classified tables of counts, commonly referred to as contingency tables. Until recent years the statistical and computational techniques available for the analysis of cross-classified data were quite limited. This book presents some of the recent work on the statistical analysis of cross-classified data using longlinear models, especially in the multidimensional situation.
Two-Dimensional Tables -- Three-Dimensional Tables -- Selection of a Model -- Four- and Higher-Dimensional Contingency Tables -- Fixed Margins and Logit Models -- Causal Analysis Involving Logit and Loglinear Models -- Fixed and Random Zeros.
Keywords: Statistics .; Statistical Theory and Methods